Modeling Maximum Entropy and Mean-Field Interaction in Macroeconomics - Corrado Di Guilmi; Mauro Gallegati; Simone Landini (Kiel Institute for the World Economy (IfW), 2008)
The representation of the economic system, from a complexity perspective, focuses on interactions among heterogeneous agents in conditions of uncertainty. Heterogeneity entails asymmetric reactions to shocks and, through interaction mechanisms and feedback loops at micro, macro and meso level, these diverse reactions influence behaviours of other agents. Such a system cannot be modelled with mainstream economics' tools. In this work we propose a stochastic dynamic model with heterogeneous firms. Their responses to stochastic shocks, in order to maximize profit, modifies their financial ratios, determining in this way the evolution of the system. The model is analytically solved by means of maximum entropy maximization and master equation's solution techniques (Aoki and Yoshikawa, 2006).
Keywords: E6; E1; 330; Business cycles; heterogeneity; financial fragility; stochastic aggregation; Konjunkturtheorie; Makroökonomik; Agent-based Model; Finanzierung; Stochastischer Prozess; Entropie; Gleichgewicht; Theorie; Master equation